Five Little-Known Facts about International Student Mobility to the United Kingdom - Ilieva, Janet (International Higher Education, 2019)
This article identifies analytical facts about international student mobility to the United Kingdom that have received little or no attention to date. It considers the implications of the relatively shorter duration of higher education degrees in the United Kingdom, the impact of poststudy work opportunities on global international student demand, sustainability of UK research degrees, and the growth in transnational education.